Fast Pyrolysis of Spent Coffee Grounds Using Fluidized-Bed Reactor - Ngo, Thanh An; Dang, Minh Chau (Old Journal, 2017)
In this research, a system of fluidized-bed pyrolysis with capacity 100 g/h was used to investigate the affects of the feedstock feed rate, pyrolysis temperature, the flow rate of the fluidizing gas, and biomass particle size on the yield of liquid product. Combining the result of experiment and central composite rotatable designs (CCRD) to determine the optimum value. It has been shown that, under conditions investigated, the maximum yield is obtained 45,03 wt% at 27 rpm, $500^{°}C$ 6 l/min, $500~μ m.$ Also, the characteristics of bio-oil such as higher heating value (HHV), viscosity, moisture content, etc were also analyzed in this research.